The perfect pair! purses, handbags, and wallets for all occasions - Ventura, Marne (North Mankato, Minnesota : Capstone Press, a Capstone imprint, [2017])
"Step-by-step instructions teach readers how to create purses, handbags, wallets, and other fashion accessories"-
A gift from book Africa
Handcrafts
1 2 13
Keywords: Handbags -- Juvenile literature; Handicraft -- Juvenile literature; Wallets -- Juvenile literature